Biology and Management of Dodder (Cuscuta spp.) in Ornamental Crop Production and Landscapes - Kaley Mierek; Stephen Christoper Marble; Nathan S. Boyd; Shawn T. Steed (EDIS)
Dodder are a group of over 150 species in the genus Cuscuta. This 4-page publication was developed to help commercial growers, landscape professionals, and homeowners identify and manage dodder infestations in their greenhouses, nurseries, or landscapes. Written by Kaley Mierek, Chris Marble, Nathan Boyd, and Shawn Steed and published by the UF/IFAS Environmental Horticulture Department, May 2018. https://edis.ifas.ufl.edu/ep556